Nepal’s Free Health Care Policy in Practice: Perspectives from Community Stakeholders, Providers and Users of Health Services in Myagdi District - Shiva Subedi (Dhaulagiri Journal of Sociology and Anthropology, 2015)
Government of Nepal has introduced Free Health Care Policy (FHCP) through different tiers of health delivery system in 2007. With the objective of understanding the perspectives of community stakeholders, health service providers, and the services users towards free care policy, a qualitative-quantitative study was conducted in selected communities of Myagdi district from December 2010 to January 2011. Although the majority of user group thought that free care service is good but only two-third of them had received free care. Shortage of free essential drugs at health facility centers, absence of health workers   and lack of clear information about free services or counseling on free services available at health facility centers are the most repeated issues raised by the service users. Similarly, the service providers had similar experiences and perceptions on FHCP. The majority of the community stakeholders also had positive perception on this implemented policy. They have observed that many facilities had shortage of drugs and people are not having free health care. Many health facilities lacked interaction on FHCP, and service users did not have equitable access to the services provided. Overall, though the free care was perceived to be good policy, its satisfactory implementation remains one of the challenges. Many of the areas relating to service delivery need to be strengthened. A reliable supply system of drugs and its regular monitoring mechanism can ensure the effective implementation of free health care services.